(untitled) - Peck, Roxy (Belmont, CA, 2008)
The book provides a look at statistics beyond simple numbers and shows how to understand the real data seen in articles, TV reports, and academic papers to make more effective personal, business, financial, and voting decisions. For undergraduate students in introductory statistics courses. Includes index, appendices, and chapter exercises with answers
Keywords: Statistics,Mathematical statistics,Thống kê,Thống kê toán học